Emergence and Generic Development of the Russian Tale - Титова, Любовь (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The author discusses one aspect of the formation and development of democratic narrative prose of the 17th century: the creation of fictional compositions on the basis of didactic texts. The study material are ‘Beseda ottsa s synom o zhenskoi zlobe’ and the cycle ‘Povesti o khmele.’